2009
DOI: 10.1093/cvr/cvp184
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase activates macrophage PON2 gene transcription via the PI3K/ROS/MEK/SREBP-2 signalling cascade mediated by the PDGFR-β

Abstract: These findings provide a framework linking interactions among cellular signalling pathways associated with reactive oxygen species production, macrophage cholesterol biosynthesis, and cellular PON2 expression in vascular pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 36 publications
2
30
0
3
Order By: Relevance
“…However, one obvious difference is the level to which the two PONs are overexpressed in cancer tissues, as this was usually much higher for PON3. Little is known about regulatory pathways controlling PON2 and especially PON3 expression, with PON2 responding to AP-1/JNK signaling, 25 PI3K/PDGFR-b 26 and ER stress, 14 while differences exist in their response, for example, to oxidative stress 27 or high-fat, high cholesterol diet. 7 Expression of PON2 and PON3 in response to inflammatory mediators such as LPS, TNF-a, IFN-g or IL-1b remains somewhat controversial; 28,29 however, the expression did not appear to have a major impact on the systems tested.…”
Section: Discussionmentioning
confidence: 99%
“…However, one obvious difference is the level to which the two PONs are overexpressed in cancer tissues, as this was usually much higher for PON3. Little is known about regulatory pathways controlling PON2 and especially PON3 expression, with PON2 responding to AP-1/JNK signaling, 25 PI3K/PDGFR-b 26 and ER stress, 14 while differences exist in their response, for example, to oxidative stress 27 or high-fat, high cholesterol diet. 7 Expression of PON2 and PON3 in response to inflammatory mediators such as LPS, TNF-a, IFN-g or IL-1b remains somewhat controversial; 28,29 however, the expression did not appear to have a major impact on the systems tested.…”
Section: Discussionmentioning
confidence: 99%
“…receptor-␤, 16,18 it is hard to predict which adaptor protein could possibly mediate the effect of uPA-uPAR interaction on PON1 expression in hepatocytes. This question will be pursued experimentally in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that in macrophages, uPA activates the NADPH oxidase complex, resulting in reactive oxygen species production, 15 and increases the expression of macrophage paraoxonase 2 (PON2), another member of the paraoxonase family. 16 We further hypothesize that uPA may promote oxidative stress in the arterial wall, also via modulation of PON1 activity. uPA is present in a variety of cells and is known to fulfill many functions through its biological activity, including intracellular signaling from the uPA/uPAR interaction.…”
mentioning
confidence: 83%
See 2 more Smart Citations